2019
DOI: 10.3390/app9245325
|View full text |Cite
|
Sign up to set email alerts
|

Potential Applications of Clay-Based Therapy for the Reduction of Pesticide Exposures in Humans and Animals

Abstract: The risk of pesticide exposure in humans and animals may be magnified following natural and man-made disasters such as hurricanes and floods that can result in mobilization and redistribution of contaminated sediments. To develop broad-acting sorbents for mixtures of diverse toxins, we have processed calcium and sodium montmorillonite clays with high concentrations of sulfuric acid. These acid-processed montmorillonite clays (APMs) have shown limited hydration and swelling in water, higher surface areas, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Previously, montmorillonite clays have been shown to be safe for human and animal consumption based on numerous animal models and human intervention studies in Africa and the United States. The efficient adsorption of CM for multiple environmental contaminant chemicals has been reported, including mycotoxins, pesticides, and PCBs. ,,,, To further investigate the adsorption efficacy of CM for more chemicals (plasticizers, PAHs, industrial solvents, and pesticides), in this study, isothermal analyses were conducted and calculated using Freundlich or Langmuir models based on the correlation coefficient. The plots of adsorption isotherms of chlorpyrifos, phenol, and naphthalene onto CM surfaces fit the Langmuir model as indicated by the correlation coefficients ( r 2 > 0.85) and curved shapes, indicating the presence of saturable sites.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, montmorillonite clays have been shown to be safe for human and animal consumption based on numerous animal models and human intervention studies in Africa and the United States. The efficient adsorption of CM for multiple environmental contaminant chemicals has been reported, including mycotoxins, pesticides, and PCBs. ,,,, To further investigate the adsorption efficacy of CM for more chemicals (plasticizers, PAHs, industrial solvents, and pesticides), in this study, isothermal analyses were conducted and calculated using Freundlich or Langmuir models based on the correlation coefficient. The plots of adsorption isotherms of chlorpyrifos, phenol, and naphthalene onto CM surfaces fit the Langmuir model as indicated by the correlation coefficients ( r 2 > 0.85) and curved shapes, indicating the presence of saturable sites.…”
Section: Resultsmentioning
confidence: 99%
“…The K d values derived in this study are indicated with an asterisk (“*”) in Table . All other K d values listed in Table were derived in previous studies. ,,,, …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since microcystins are also commonly found as contaminants of food, there is a need for effective dietary treatments that will reduce human and animal exposures from the diet. On the basis of the literature, microcystins are adsorbed strongly to sediment and are difficult to recover , and the adsorption is more effective by montmorillonite clays than other clay minerals. , Montmorillonite clay is the mineral in the smectite group of phyllosilicates with a stable porous structure, high expandability, specific surface area, and cation exchange capacity due to negative charge on the siloxane surface, enabling its application as a toxin binder. Using dietary montmorillonite clay as a detoxification strategy for MC-LR is a logical spinoff from our previous human clinical trials in the U.S. and Africa, where we reported that quality-controlled montmorillonite inclusion in the diet and drinking water was effective in binding a foodborne mycotoxin in the gastrointestinal tract and was safe for consumption in adults and children. , Therefore, in this study, we characterized the binding interactions of MC-LR on the surfaces of montmorillonites by in vitro adsorption equilibrium analyses and thermodynamics, and in silico computational modeling.…”
Section: Introductionmentioning
confidence: 99%